Religious Moderation in Islamic Boarding School-Based International Educational Institutions in Indonesia - Bakhruddin, Mukhammad; Fatimatur Rusydiyah, Evy; Akhmad Taufiq, Mirwan; Wahid Nur Tualeka, Muhamad; Syaifudin, Mochamad; Syaikhon, Muhammad (Bahasa Indonesia, Bahasa English, 2025)
This study analyzes the implementation of religious moderation in international Islamic boarding schools in Indonesia using the national framework of religious moderation, which comprises moderation of thought, movement, and action. Employing a qualitative multiple-case study design, the research examines two institutions in Malang International Islamic Boarding School (IIBS) Al Izzah and IIBS Thursina through in-depth interviews, participant observation, and documentation analysis. Data were analyzed thematically using a framework-based approach guided by the interactive model of Miles and Huberman. The findings reveal that religious moderation is implemented in an integrated and contextual manner. Moderation of thought is reflected in the alignment of Islamic teachings with national ideology and civic values. Moderation of movement is manifested through daily social practices that promote tolerance and dialogue. Moderation of action is evident in the rejection of violence and the selective accommodation of local culture in accordance with Islamic principles. Overall, the study challenges perceptions of international pesantren as exclusive institutions and highlights their role in fostering inclusive and peaceful religious life in Indonesia.